Downmodulation of peripheral MUG-specific immunity by pVAXhspe65 treatment during EAE does not reach the CNS - Goncalves Zorzella-Pezavento, Sofia Fernanda [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Donega Franca, Thais Graziela [UNESP]; Watanabe Ishikawa, Larissa Lumi [UNESP]; Rosa, Larissa Camargo da [UNESP]; Colavite, Priscila Maria [UNESP]; Marques, Camila; Valerio Ikoma, Maura Rosane; Silva, Celio Lopes; Sartori, Alexandrina [UNESP] (Elsevier B.V., 2014)
Most of the therapeutic strategies to control multiple sclerosis are directed to immune modulation and inflammation control. As heat shock proteins are able to induce immunoregulatory T cells, we investigated the therapeutic effect of a genetic vaccine containing the mycobacterial hsp65 gene on experimental autoimmune encephalomyelitis (EAE). Although pVAXhsp65 was immunogenic for mice with EAE and downmodulated specific cytokine induction by MOG, therapy was not able to decrease clinical severity nor to modify immunologic parameters in the CNS. These results indicate that hsp65, administered as a DNA vaccine, was not therapeutic for EAE. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Experimental autoimmune encephalomyelitis hsp65; DNA vaccine; CD4+CD25+Foxp3+T cells